Revalidation of the genus Thoracophelia Ehlers, 1897, replacing Euzonus Grube, 1866 (Polychaeta: Opheliidae), junior homonym of Euzonus Menge, 1854 (Arthropoda: Diplopoda), together with a literature summary and updated listing of Thoracophelia species - Blake, James A. (Zootaxa, 2011)
Begins: Brewer et al. (2011) recently demonstrated that the generic name Euzonus was being used in both Arthropoda (Diplopoda) and Polychaeta (Opheliidae) systematics and that the arthropod name was the senior synonym. The diplopod name Euzonus Menge, 1854, based on a single species, E. collulum Menge, 1854 from Baltic amber predates Euzonus Grube, 1866, established for E. arcticus Grube, 1866 from the Arctic Ocean. The Nomenclator Zoologicus (2005) verifies that both names are listed as uncorrected homonyms. Brewer et al. (2011) suggested that for time being, the genus Pectinophelia Hartman, 1938 could be used for those species of Polychaeta currently referred to the genus Euzonus. However, prior to Hartman’s (1956) referral of these opheliids to the genus Euzonus, some species had been included in the genus Thoracophelia Ehlers, 1897 and this is clearly the next available name for polychaetes currently referred to Euzonus Grube. In the following paragraphs I summarize some key decision points in the taxonomic history of these opheliids, their referral to Thoracophelia, and why subgenera, as currently applied, are not necessary.
CIM-ID: 15924 Open access article